The Effect of Protease-Activated Receptor-1 (PAR-1) Inhibition on Endothelial-Related Biomarkers in Patients with Coronary Artery Disease - Nilsen, Dennis W. T.; Røysland, Michelle; Ueland, Thor; Aukrust, Pål; Michelsen, Annika E.; Staines, Harry; Barvik, Ståle; Kontny, Frederic; Nordrehaug, Jan Erik; Bonarjee, Vernon V. S. (Thrombosis and Haemostasis, 2022)
Background Vorapaxar has been shown to reduce cardiovascular mortality in post-myocardial infarction (MI) patients. Pharmacodynamic biomarker research related to protease-activated receptor-1 (PAR-1) inhibition with vorapaxar in humans has short follow-up (FU) duration and is mainly focused on platelets rather than endothelial cells.Aim This article assesses systemic changes in endothelial-related biomarkers during vorapaxar treatment compared with placebo at 30 days' FU and beyond, in patients with coronary heart disease.Methods Local substudy patients in Norway were included consecutively from two randomized controlled trials; post-MI subjects from TRA2P-TIMI 50 and non-ST-segment elevation MI (NSTEMI) patients from TRACER. Aliquots of citrated blood were stored at –80°C. Angiopoietin-2, angiopoietin-like 4, vascular endothelial growth factor, intercellular adhesion molecule-1, vascular cell adhesion molecule-1, E-selectin, von Willebrand factor, thrombomodulin, and plasminogen activator inhibitor-1 and -2 were measured at 1-month FU and at study completion (median 2.3 years for pooled patients).Results A total of 265 consecutive patients (age median 62.0, males 83%) were included. Biomarkers were available at both FUs in 221 subjects. In the total population, angiopoietin-2 increased in patients on vorapaxar as compared with placebo at 1-month FU (p = 0.034). Angiopoietin-like 4 increased (p = 0.028) and plasminogen activator inhibitor-2 decreased (p = 0.025) in favor of vorapaxar at final FU. In post-MI subjects, a short-term increase in E-selectin favoring vorapaxar was observed, p = 0.029. Also, a short-term increase in von Willebrand factor (p = 0.032) favoring vorapaxar was noted in NSTEMI patients.Conclusion Significant endothelial biomarker changes during PAR-1 inhibition were observed in post-MI and NSTEMI patients.
Keywords: PAR-1 inhibition; vorapaxar; myocardial infarction (MI); post-MI; NSTEMI; biomarkers; endothelium